Hello!
To find the quadrant of where the angle 7π/6 radians is located, we will need to convert from radians to degrees. To do that, we will need to multiply it by 180/π.
7π/6 × 180/π = 1260/6 = 210 degrees
Since 210° is between 180° and 270°, then 7π/6 radians is located in the third quadrant shown by: Quadrant III, then 180° < θ < 270°.
Therefore, 7π/6 radians is located in quadrant III.
<h3>:- Solution</h3>
-8x - 9 > -21
Move -9 to right side
-8x > -21 + 9
-8x > -12
x < -12/-8
x < 3/2
the answer to -8x - 9 > -21 is <u>x</u><u> </u><u><</u><u> </u><u>3</u><u>/</u><u>2</u>
First do 10 time 10, which gives you a hundred, then add two, and you get 102
Answer:
![P(Service\ Brokerage\ or\ Online) = 66\%](https://tex.z-dn.net/?f=P%28Service%5C%20Brokerage%5C%20or%5C%20Online%29%20%3D%2066%5C%25)
Step-by-step explanation:
Given
![P(Service\ Brokerage) = 60\%](https://tex.z-dn.net/?f=P%28Service%5C%20Brokerage%29%20%3D%2060%5C%25)
![P(Online) = 30\%](https://tex.z-dn.net/?f=P%28Online%29%20%3D%2030%5C%25)
![P(Both) = 24\%](https://tex.z-dn.net/?f=P%28Both%29%20%3D%2024%5C%25)
Required
Determine P(Service Brokerage or Online)
In probability:
![P(A\ or\ B) = P(A) + P(B) - P(Both)](https://tex.z-dn.net/?f=P%28A%5C%20or%5C%20B%29%20%3D%20P%28A%29%20%2B%20P%28B%29%20-%20P%28Both%29)
In this case:
![P(Service\ Brokerage\ or\ Online) = P(Service\ Brokerage) + P(Online) - P(Both)](https://tex.z-dn.net/?f=P%28Service%5C%20Brokerage%5C%20or%5C%20Online%29%20%3D%20P%28Service%5C%20Brokerage%29%20%2B%20P%28Online%29%20-%20P%28Both%29)
Substitute values:
![P(Service\ Brokerage\ or\ Online) = 60\% + 30\% - 24\%](https://tex.z-dn.net/?f=P%28Service%5C%20Brokerage%5C%20or%5C%20Online%29%20%3D%2060%5C%25%20%2B%2030%5C%25%20-%2024%5C%25)
![P(Service\ Brokerage\ or\ Online) = 66\%](https://tex.z-dn.net/?f=P%28Service%5C%20Brokerage%5C%20or%5C%20Online%29%20%3D%2066%5C%25)
<em>Hence, the required probability is 66%</em>
Answer:
the value of x that makes this equation true is 9
Step-by-step explanation:
2(x - 6) + x + 14 = 4(x - 3) + 5
<em>open the parenthesis</em>
2x - 12 + x + 14 = 4x - 12 + 5
<em>add 12 to both sides of the equation</em>
2x - 12 + 12 + x + 14 = 4x - 12 + 12 + 5
2x + x + 14 = 4x + 5
<em>subtract 5 from both sides of the equation</em>
2x + x + 14 - 5 = 4x + 5 - 5
3x + 14 - 5 = 4x
3x + 9 = 4x
<em>subtract 3x from both sides of the equation</em>
3x - 3x + 9 = 4x - 3x
9 = 4x - 3x
9 = x
check the answer:
2(x - 6) + x + 14 = 4(x - 3) + 5
2(9 - 6) + 9 + 14 = 4(9 - 3) + 5
29 = 29